THE EFFECTIVENESS OF MARKETING COMMUNICATION IN DIGITAL BUSINESS: A CASE STUDY OF MARKETING ON TIKTOK LIVE - Mawaddah, Mawaddah; Wulandari, Poppy; Panjaitan, Andreas; Dwianita, Dwianita (Jurnal Ilmu Komunikasi, 2025)
This research examines the effectiveness of marketing communication through TikTok Live, focusing on its impact on consumer engagement and purchase decisions. As digital business in Indonesia rapidly grows, TikTok has evolved from an entertainment platform to a dynamic marketing tool, integrating e-commerce and live commerce features. By allowing real-time interactions between brands and consumers, TikTok Live enhances trust, fosters deeper engagement, and encourages impulsive purchases. The study finds that the interactive nature of TikTok Live, including live demonstrations and direct consumer inquiries, significantly influences purchasing behavior. Additionally, the integration of entertainment elements further strengthens consumer interest and increases conversion rates. The research adopts a qualitative approach, using a case study design with participatory observation and content analysis of several TikTok Live sessions to identify key factors influencing consumer decisions. The findings highlight the potential of TikTok Live as a powerful platform for both large and small businesses to enhance marketing effectiveness and reach a broader audience, especially younger consumers. In conclusion, businesses looking to optimize their digital marketing strategies should leverage TikTok Live’s real-time, interactive features to create more personalized, engaging consumer experiences.